Enhancing the Implementation of PCG NSTP-CWTS: Perceptions, Challenges, and Recommendations - Pangilinan, Elaine R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assessed the Philippine Coast Guard (PCG) National Service Training Program-Civic Welfare Training Service (NSTP-CWTS) program through identification of the demographic profile of the students and instructors. It also examined the student’s perception of the delivery, support system, and teaching outcome. The instructors assessed the program’s content and support system and identified the challenges they experienced. The study revealed the relationship between the challenges experienced by the instructors when grouped according to profile. The study used a quantitative-correlational research design using a researcher-made questionnaire to gather data from 251 students and 31 instructors from selected institutions where PCG has a memorandum of agreement for providing the program. The data showed that students were male second-years enrolled in maritime courses who attended primarily face-to-face classes. The instructors were mostly junior-ranked with limited years of service and little to no NSTP-CWTS-specific training. The students’ perception was generally positive. The instructors had effective communication, and the program was aligned with the training objectives, although concerns were raised about the sufficiency of the allocated time and adequacy of training materials. The curriculum was aligned with the national. The challenges experienced include resource availability, graduate deployment, and institutional collaboration with universities and LGUs. It was revealed significant relationships between the challenges experienced and specific demographic aspects such as unit assignment and years in service. The study suggested strengthening institutional partnerships, instructor training and development, improving logistical support, structuring the graduate deployment process, and program modification to match students' diversity and career aspirations.